2016
DOI: 10.1093/cid/ciw016
|View full text |Cite
|
Sign up to set email alerts
|

A Necrotizing Enterocolitis-Associated Gut Microbiota Is Present in the Meconium: Results of a Prospective Study

Abstract: CALIFORNIA trial, registered under trial number NTR4153 in the Dutch Trial Registry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
113
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(122 citation statements)
references
References 37 publications
1
113
3
1
Order By: Relevance
“…found increasing incidence rates of NEC in the most preterm and low birthweight infants in three centres in the Netherlands, when guidelines changed towards active treatment at lower gestational ages. 222 In contrast to our results, no increase was seen in the term, near term or normal birthweight advances in neonatal care, causing an initial reduction in NEC incidence followed by an increase as the early survival in the population at risk improved, may eventually transition to a phase of stabilised or even decreasing incidence, when some of the prophylactic measures learned along the way gain effect. 9 which is a matter of definition.…”
Section: Variations Over Time and Between Populationscontrasting
confidence: 99%
See 2 more Smart Citations
“…found increasing incidence rates of NEC in the most preterm and low birthweight infants in three centres in the Netherlands, when guidelines changed towards active treatment at lower gestational ages. 222 In contrast to our results, no increase was seen in the term, near term or normal birthweight advances in neonatal care, causing an initial reduction in NEC incidence followed by an increase as the early survival in the population at risk improved, may eventually transition to a phase of stabilised or even decreasing incidence, when some of the prophylactic measures learned along the way gain effect. 9 which is a matter of definition.…”
Section: Variations Over Time and Between Populationscontrasting
confidence: 99%
“…Case-control, N=720 Manually identified, N=200 p n (%) n (%) (222)(223)(224) days respectively. The strongest factor for infants to lack registrations in the NPR, however, was in hospital death.…”
Section: Comparison Of Nec Cases In the Case-control Cohort And Manuamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a recent randomized controlled trial on preterm piglets demonstrated sustained administration of antibiotics initiated directly after birth to be protective against NEC [19]. Moreover, in a recent study by Heida et al [20], a NEC-associated gut microbiota composition was already observed to be present in the meconium. These observations, in combination with the absence of any association between the development of NEC and the total number of days treated with antibiotics suggest that, in particular, initial intestinal colonization plays an essential role in the pathogenesis of NEC.…”
Section: Discussionmentioning
confidence: 97%
“…However, recent data prompt reconsideration of this dogma. Mshvildadze et al [1] identified bacterial sequences in freshly produced meconium, as have Heida et al [2], and Ardissone et al [3]. Stout et al [4] have identified bacterial bodies on electron microscopy in the basal plate of placentas delivered via cesarean section.…”
Section: The In-population Of the Human Infant Gut By Microbesmentioning
confidence: 99%